PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, LEVERAGE, DAN KEPEMILIKAN INSTITUSIONAL TERHADAP PERATAAN LABA: Studi Empiris pada Perusahaan Food and Beverages yang Terdaftar di BEI - Butar Butar Linda Kurniasih; Sudarsi Sri (Dinamika Akuntansi Keuangan dan Perbankan, 2012)
The aims of this research was to prove the influence of  size company, profitability, leverage, institutional ownership toward the income smoothing. Income smoothing is practice used by managers of a company to reduce the fluctuation of the reported income to achieve the target income either artificial or naturally. Index Eckel (1981) was used to determine the income smoothing. This research was carried out by using 12 food and beverages companies listed in Indonesia Stock Exchange during 4 years period from 2005 until 2008. The hypotheseses were tested using binary logistic regression. The result’s shows that the size of company was significant influence to income smoothing. The influence of profitability, leverage, institutional ownership was not significant. Key words: the size of company, profitability, leverage, institutional ownership, income smoothing